Ancient Greek Theatre and Agonistic Culture - Özge Acar (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
This article explores Ancient Greek theatre through the agons, which played an essential role in the culture of Greek society. The history of Greek theatrical performances goes back much further than the emergence of tragedy and comedy as a genre. Therefore, the term Greek theatre in this study refers not only to Classical Greek drama, but also to the whole artistic activity that takes place in the theatre as a venue; in other words, to the Greek mousike. The Greek musical agons were the most crucial element that conveyed this cultural accumulation up to the Roman Imperial Period. This study introduces an overview of the musical agons from the Archaic Period to the Roman Empire. Analyzing the accounts of ancient authors and epigraphic documents together, it is observed that these musical agons were characterized by the ever-changing sociopolitical conditions of each period.